The lack of systems thinking and interdisciplinarity is killing the hydrogen economy - Marnate, Kumail (Frontiers in Energy Research, 2025)
Hydrogen’s promise as a transformative energy solution has been consistently unfulfilled. This perspective article suggests that the primary barrier is not necessarily technological, but a systemic failure to apply holistic systems thinking and genuine interdisciplinary collaboration. Through historical analysis and contemporary case studies, we argue that only by integrating technical, economic, policy, and social expertise within a holistic systems framework across the entire value chain can hydrogen overcome its boom-and-bust cycles and become a foundational component of the low-carbon energy future.